Impact of sustainable forest management practices on forest certification, plantation and trade of forest products - Abd Wahob, Noraida (2020)
The natural forest around the world continues to be degraded and destroyed at a rapid pace on an annual basis. The declining of natural forests is due to its poor management. Therefore, forest certification and forest plantation are seen as the most comprehensive strategies to promote better forest management and growth. The comprehensive strategies will not succeed if the producer or the forest owner tend to have uncertainty about their gain from forest certification and plantation. This thesis is based on an essay that constitutes three different essays that investigate the determinant of forest certification, forest plantation and the impacts of forest certification as well as a plantation on international trade of forest products among members of the International Timber Trade Organization (ITTO). The study in the first two essays, use a dynamic panel of Generalized Method of Moments (GMM). The data used were panel data series derived from 2011 until 2017, which referred five sources, namely, World Development Indicators (WDI), Worldwide Governance Indicators (WGI), Food and Agricultural Organizations (FAO) and annual year report from the Forest Stewardship Council (FSC) as well as International Country Risk Guide (ICRG). While the third essay used forecasting method known as Global Forest Products Model (GFPM). This research adapts an extensive database of panel data consisting of 73 ITTO countries from 1980 to 2015. The estimated results for the determinants of forest certification reveal that economic incentive and environmental aspect significantly increases of forest certification in all the ITTO countries. It suggested that policy makers in ITTO organization need to strengthen the commitment to permit the international trade in tropical timber from sustainably managed and only legally harvested forests. On the determinants of forest plantation outcomes, the result shows the reforestation delay and economic incentive significantly determine the growth of forest plantation among ITTO countries. The finding proposes that, ITTO organization need to encourage fast-growing species for industrial forest plantations in tropics and promote the sustainable management of tropical timber. Lastly, the results of the impact of forest certification and plantation toward forest product trade, disclose forest certification and plantation have a crucial effect on the forest product trade at the national level, depending on the percentage of forest certification and plantation area each country possesses. The general findings indicate environment and economic incentives play a main role in enhancing the growth of forest certification and plantation among the ITTO countries. The government must take an active role and efficient steps in strengthening the growth of the forests by encouraging more forest owners to apply for forest certification and increase the number of forest plantation. The initiated efforts would generate a stable economic growth in forest product trade in, in par with sustainability. The results will serve as parameters that directly determines the well-being of forest products among ITTO countries and enhance the forest conservation goals of each ITTO members.